Taguchi Method for Development of Mass Flow Rate Correlation using Hydrocarbon Refrigerant Mixture in Capillary Tube - Shodiya Sulaimon; Henry Nasution; Azhar Abdul Aziz; Abdul-Halim Abdul-Rahman; Amer N. Darus (Journal of Engineering and Technological Sciences, 2014)
The capillary tube is an important control device used in small vapor compression refrigeration systems such as window air-conditioners, household refrigerators and freezers. This paper develops a non-dimensional correlation based on the test results of the adiabatic capillary tube for the mass flow rate through the tube using a hydrocarbon refrigerant mixture of 89.3% propane and 10.7% butane (HCM). The Taguchi method, a statistical experimental design approach, was employed. This approach explores the economic benefit that lies in studies of this nature, where only a small number of experiments are required and yet valid results are obtained. Considering the effects of the capillary tube geometry and the inlet condition of the tube, dimensionless parameters were chosen. The new correlation was also based on the Buckingham Pi theorem. This correlation predicts 86.67% of the present experimental data within a relative deviation of -10% to +10%. The predictions by this correlation were also compared with results in published literature.